Pengaruh Kandungan Obat Demam Sirup Terhadap Kasus Gagal Ginjal Akut Pada Anak - Salman Salman; Shiyami Aulia Nur Darmawan; Nina Elyyana; Syifa Khairunnisa; Anggi Ayu Pratama; Tiara Nurayuni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Kidney failure is a condition when the kidneys cannot function properly to filter or remove waste from the body. This study aimed to determine the solvents in syrup fever drugs, namely ethylene glycol and diethylene glycol, which are suspected of causing acute kidney failure in children. The method is to collect journals from various databases such as Google Scholar, PubMed, NCBI, and others. The results of ethylene glycol (EG) and diethylene glycol (DEG) in fever syrup can affect damage the kidneys if their administration exceeds the threshold. The formation of oxalic acid metabolites from ethylene glycol can precipitate into calcium oxalate monohydrate crystals in the tubules’ lumen, which triggers kidney stones and acute kidney injury. In Diethylene Glycol, the formation of metabolites of 2-hydroxyethoxyacetic acid (HEAA) has. Toxic effects resulting from the buildup of HEAAs cause acidosis and kidney organ failure.